Competencia desleal por actos de engaño e imitación : estudio comparado España, Estados Unidos y Puerto Rico - Echegaray Daleccio, Fernando Juan (Colección Instituto de Derecho Comparado (Dykinson), 2022)
Law 3/1991, of January 10th, has meant a huge advance in the regulation of the unfair competition in Spain, because until that date, the number of effective legal dispositions to regulate that matter was scarce and had little relevance in practice. This law was created to protect and prevent the violation of the right to free competition, as set out in article 38 of the Spanish Constitution. Subsequently, to adapt community legislation into line with our law, Law 29/2009, of December 30th, was approved, being the legislation which is currently in force, amending the system of unfair competition and advertising in order to improve the protection of the consumers and users. On the other hand, we will focus on explaining one of the many types of unfair acts typified by the unfair competition law, acts of deceptions, specifically between businessmen. Their prohibition is based on the fact that they harm all market participants and the proper functioning of the market, which must be based on honesty and transparency.